Analysis of Behavioral Accounting Aspects in Cost Control at LKP Polindo Internasional - Eka Mayasari; Sri Trisnaningsih (Institut Teknologi dan Bisnis (ITB) Semarang, 2024)
This research aims to examine the analysis of behavioral accounting aspects in cost control at LKP Polindo Internasional. The study utilizes a case study approach. Data collection techniques involve gathering articles and journals, as well as conducting observations and interviews with managers and financial stakeholders at LKP Polindo Internasional. Several articles used for discussion topics were obtained from Google Scholar, relating to the behavioral accounting aspects in cost control. The research findings indicate that the implementation of budgeting by LKP Polindo Internasional is one of the methods used to allocate company costs effectively and efficiently, and it has been well implemented. By utilizing budgeting, the company can have a more precise overview of the costs associated with various activities within the company. The budget serves as a reference for carrying out future activities. This research is expected to provide insights into the positive contribution of implementing Behavioral Accounting and Activity-Based Costing Systems in cost control for educational service institutions or companies. However, this study has limitations, including constraints on data availability from the company and limitations on generalizing research findings to other organizations. Additionally, external factors that may affect cost control could also pose limitations.